Technology Acquisition and Knowledge Networks : Knoweldge Economy Forum VI, Cambridge, United Kingdom - World Bank (World Bank, Washington, DC, 2013)
The paper is a report to cover the proceedings of the Knowledge Economy Forum VI held in Cambridge, UK in 2007. This report encapsulates the end product of the conference with regard to the current state of the European knowledge economy, especially in Eastern Europe.